Review on Heart Diseases Prediction on ANN - Yadav, Vijay; Tiwari, Ashish (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2016)
Neural network (ANN) tool has been used for solving many decision modeling problems. A multilayer perception is a feed forward ANN model that is used extensively for the solution of heart diseases problems. An ANN is the same as human brain. This is a non-linear classification monitoring learning technique used for coronary heart disease is the biggest epidemic the world is at risk of coronary heart disease. Most doctor's diagnosis is made by clinical expertise and patients were asked to take someone. Diagnostic testing. But all the tests will not contribute to diagnosis of the disease effectively. Feature subset selection, dimensionality used to remove irrelevant data to reduce a preprocessing step. In this paper we have a classification approach to the classification of heart disease ANN uses features from subset selection. Properties which indirectly reduces. Diagnostic tests which need to be taken by the patient. We applied our approach to heart disease data base. Our experimental results show that the accuracy improves with conventional classification techniques. This system is possible and for faster and more accurate diagnosis of heart disease.